Membaca Opera Batak Lakon Perempuan di Pinggir Danau Produksi Pusat Latihan Opera Batak - Lismade Soraya Juliana Siagian (Institut Seni Indonesia Yogyakarta, 2019)
Opera Batak is one of theatre in Indonesia. This research about dramaturgy of Opera Batak. The Dramaturgy of Opera Batak Perempuan di Pinggir Danau, PLOt production at North Sumatera, begins with understanding the staging of more than understanding a written text by using the theoretical basis of theater dramaturgy by Euginio Barba and research of qualitative methods. This research has been doing for two month at Pematang Siantar, North Sumatera district where Batak Opera originally come from. This research aims to dig about structure and tecstur, and the theatre elements from the performance. Opera Batak PLOt production in the group play Perempuan di Pinggir Danau that the form of theater based on traditional Batak area for the Batak society as a medium of entertainment and messaging truths of life.Keywords: theatre; dramaturgy; Opera Batak